Glacier fluctuations during the past 2000 years. (1st October 2016) - Solomina, Olga N.; Bradley, Raymond S.; Jomelli, Vincent; Geirsdottir, Aslaug; Kaufman, Darrell S.; Koch, Johannes; McKay, Nicholas P.; Masiokas, Mariano; Miller, Gifford; Nesje, Atle; Nicolussi, Kurt; Owen, Lewis A.; et al.
Abstract: A global compilation of glacier advances and retreats for the past two millennia grouped by 17 regions (excluding Antarctica) highlights the nature of glacier fluctuations during the late Holocene. The dataset includes 275 time series of glacier fluctuations based on historical, tree ring, lake sediment, radiocarbon and terrestrial cosmogenic nuclide data. The most detailed and reliable series for individual glaciers and regional compilations are compared with summer temperature and, when available, winter precipitation reconstructions, the most important parameters for glacier mass balance. In many cases major glacier advances correlate with multi-decadal periods of decreased summer temperature. In a few cases, such as in Arctic Alaska and western Canada, some glacier advances occurred during relatively warm wet times. The timing and scale of glacier fluctuations over the past two millennia varies greatly from region to region. However, the number of glacier advances shows a clear pattern for the high, mid and low latitudes and, hence, points to common forcing factors acting at the global scale. Globally, during the first millennium CE glaciers were smaller than between the advances in 13th to early 20th centuries CE. The precise extent of glacier retreat in the first millennium is not well defined; however, the most conservative estimates indicate that during the 1st and 2nd centuries in some regions glaciers were smaller than at the end of 20th/early 21st centuries. Other periods of glacier retreat are identified regionally during the 5th and 8th centuries in the European Alps, in the 3rd–6th and 9th centuries in Norway, during the 10th–13th centuries in southern Alaska, and in the 18th century in Spitsbergen. However, no single period of common global glacier retreat of centennial duration, except for the past century, has yet been identified. In contrast, the view that the Little Ice Age was a period of global glacier expansion beginning in the 13th century (or earlier) and reaching a maximum in 17th–19th centuries is supported by our data. The pattern of glacier variations in the past two millennia corresponds with cooling in reconstructed temperature records at the continental and hemispheric scales. The number of glacier advances also broadly matches periods showing high volcanic activity and low solar irradiance over the past two millennia, although the resolution of most glacier chronologies is not enough for robust statistical correlations. Glacier retreat in the past 100–150 years corresponds to the anthropogenic global temperature increase. Many questions concerning the relative strength of forcing factors that drove glacier variations in the past 2 ka still remain. Graphical abstract: Number of glacial advances, temperature reconstruction and climatic forcings. (A) Total solar irradiance anomalies (Steinhilber et al., 2009).(B) Reconstructed global volcanic aerosol forcing from sulfate composite records from tropical (bipolar) eruptions (Sigl et al., 2015). (C) Multi-proxy temperature reconstruction of the Northern Hemisphere (CE 1–1979 (red) with its 80-yr component (blue) and the instrumental record (green) (Moberg et al., 2005).(D ) Number of glacial advances normalized and inverted (averaged for the high and mid latitudes of the Northern and Southern hemispheres and from the tropics, cumulative curves). Highlights: The LIA was a global phenomenon with maximum extents varying in time in different regions. Global coherence of glacier advances are recognized in the 2nd millennium CE. Glacier fluctuations broadly correspond with temperature in the past 2 ka. Coherence of glacier advances with volcanic eruptions and solar variability in the past 1 ka. No analogues of modern global glacier recession is recognized in the past 2 ka.